2015
DOI: 10.3899/jrheum.150460
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Monitoring For Coronary Heart Disease Risk in Patients with Systemic Lupus Erythematosus: A Systematic Review

Abstract: Premature CHD in SLE is multifactorial; modifiable variables should be monitored at frequent intervals to ensure prompt management. Disease-specific factors also affect the atherogenic process and should be evaluated regularly. Carotid ultrasonography may hold promise in predicting CVE in selected high-risk patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
112
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(121 citation statements)
references
References 115 publications
4
112
1
4
Order By: Relevance
“…Obesity has been considered as a conventional risk factors of CVD including hypertension and coronary heart disease, and equally applied to patients with SLE . However, underweight patients or individuals with low fat composition had lower survival rate than normal or overweight populations, which is called the “obesity paradox”.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Obesity has been considered as a conventional risk factors of CVD including hypertension and coronary heart disease, and equally applied to patients with SLE . However, underweight patients or individuals with low fat composition had lower survival rate than normal or overweight populations, which is called the “obesity paradox”.…”
Section: Discussionsupporting
confidence: 49%
“…Many studies have reported a U‐shaped association with BMI and mortality risk from CVD, especially in east Asians . Here, BMI was negatively associated with cIMT increment, and the values of BMI in this study were significantly lower (21.0 ± 2.8 kg/m 2 ) than those in the studies (mean BMI, 25‐26 kg/m 2 ) assessing the risk of obesity to CVD . According to such studies, the patient population of some races including Koreans had less frequent obesity and lower BMI than Western patients.…”
Section: Discussionsupporting
confidence: 49%
“…Recently published adult guidelines recommend the following: initial risk assessment of lipid profile, blood pressure and fasting glucose assessment, tobacco exposure, and plasma homocysteine evaluation; hsCRP and SLE monitoring labs at each visit, and yearly assessment of aPL antibodies. (78)** CIMT monitoring is recommended for patients with > 1 risk factor or renal disease but their utility needs to be further validated. In childhood-onset SLE, no imaging has yet proven robust for surrogate of atherosclerosis and screening guidelines remain to be developed.…”
Section: Pathogenesis Of Premature Atherosclerosis In Slementioning
confidence: 99%
“…Among CVD, the Myocardial Infarction (MI) is the most dreaded menace. MI is prolonged ischemia with necrosis of myocytes due to interruption of blood supply to an area of heart (Kumar and Gurusamy, 2014;Tselios et al, 2016) which results in multiple biochemical alterations (Alamgeer et al, 2015).…”
Section: Introductionmentioning
confidence: 99%